VALUE-BASED EMPLOYEE RELATIONSHIP MANAGEMENT FOR PROFESSIONAL INTEGRITY IN MADRASAH EDUCATION - Holidi, Moh; Fikri, Ahmad Rausyan; Kamil, Moh.; Najiburrahman, Najiburrahman; Agus R, Abu Hasan; Dewi, Annisa Tri Ananda (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
This research focuses on the analysis of the management of relationships between employees to strengthen professional integration in Madrasas, as well as identify factors that support the creation of harmonious and ethical working relationships. The approach used is a qualitative method with case studies, which is carried out through in-depth interviews, observations, and documentation of madrasah leaders, teachers, and education staff. The results indicate that effective employee relations management is formed through transparent two-way communication, the implementation of fair work policies, a collaborative culture, and the strengthening of Islamic values in professional ethics. The findings also state that employee integrity increases when madrasahs implement a system of continuous development, proportional supervision, and the provision of rewards for performance and ethical behavior. The implications of this study indicate that strengthening professional integration depends not only on formal policies, but also on the quality of interpersonal relationships, value-oriented leadership, and a work environment that supports ethical behavior. Madrasahs are advised to strengthen employee relations programs as a strategy to improve the quality of human resources in a sustainable manner. This study contributes to Islamic educational management by demonstrating how value-based employee relationship management serves as a strategic mechanism for strengthening professional integrity in madrasah organizations.